Sustainable Supply Chain Governance Mechanisms: Strategic Approaches to Corporate Sustainability - Rajindra, Rajindra; Burhanuddin, Burhanuddin; Rukhayati, Rukhayati; Wekke, Ismail Suardi (International Journal of Supply Chain Management, 2019)
Organizations are very concerned about their reputation in the current business era. Due to high sustainability snags, the organizational image can be damaged. There is need for additional social and environmental strategies and standards to portray organizational concern towards the environment and society. Therefore, considering the investigate the nexus between supply chain management, sustainable supply chain governance and corporate suitability. The study is interested in analyzing the direct relationship between supply chain management, and corporate sustainability and between sustainable supply chain and corporate sustainability. In addition to that the current study is also interested in examining the moderating role of sustainable supply chain governance in the relationship between supply chain management and corporate sustainability. The difficulty of issues under investigation has been investigated by the use of three theoretical frameworks, which allow its understanding and facilitate the construct of clear idea about the practical perspective. In the next section, Sustainable Supply Chain Management has been defined and literature has been sourced on its different approaches along with the theoretical frameworks and mechanism of governance. The SEM-PLS is used to investigate the hypothesis relationship. Overall the findings of the study have provided support to the proposed results